2004
DOI: 10.1897/03-21
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of metals and trace elements in blood of spectacled and king eiders in northern Alaska, USA

Abstract: In 1996, we measured concentrations of arsenic, barium, cadmium, lead, mercury, and selenium in blood of adult king (Somateria spectabilis) and spectacled (Somateria fischeri) eiders and duckling spectacled eiders from northern Alaska, USA. Concentrations of selenium exceeded background levels in all adults sampled and 9 of 12 ducklings. Mercury was detected in all adult spectacled eiders and 5 of 12 ducklings. Lead concentrations were above the clinical toxicity threshold in one duckling (0.64 ppm) and two ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 31 publications
4
18
0
Order By: Relevance
“…Wayland et al (2008a) reported a mean blood Hg concentration of 0.19 lg/g wet weight (range: 0.06-0.47) in white-winged scoters in Canada. While some field studies across North America have investigated the presence of Hg in blood tissue of multiple eider species on their breeding grounds (Wilson et al, 2004;Wayland et al, 2008bWayland et al, , 2007Wayland et al, , 2001a, none have thoroughly examined the dynamics of Hg exposure in wintering eiders. It is important to consider the entire annual cycle when examining and comparing Hg values across different studies.…”
Section: Mercury In Eider Bloodmentioning
confidence: 99%
“…Wayland et al (2008a) reported a mean blood Hg concentration of 0.19 lg/g wet weight (range: 0.06-0.47) in white-winged scoters in Canada. While some field studies across North America have investigated the presence of Hg in blood tissue of multiple eider species on their breeding grounds (Wilson et al, 2004;Wayland et al, 2008bWayland et al, , 2007Wayland et al, , 2001a, none have thoroughly examined the dynamics of Hg exposure in wintering eiders. It is important to consider the entire annual cycle when examining and comparing Hg values across different studies.…”
Section: Mercury In Eider Bloodmentioning
confidence: 99%
“…High blood selenium concentrations also have been described in otherwise healthy Alaskan waterfowl including Emperor Geese (Chen canagica), Long-tailed Ducks, Spectacled Eider, King Eider (Somateria spectabilis), and Common Eider (Franson et al, 1999Stout et al, 2002;Wayland et al, 2003;Franson et al, 2004;Wilson et al, 2004). Similarly, high tissue concentrations have been described in ducks from Canada (Henny et al, 1995;Wayland et al, 2001Wayland et al, , 2003Braune and Malone, 2006) and Russia (Stout et al, 2002).…”
mentioning
confidence: 93%
“…Samples have usually been collected from nesting birds when they are most easily caught. Blood concentrations declined through the breeding period in Emperor Geese (Franson et al, 1999) and Spectacled Eiders (Wilson et al, 2004), suggesting exposure occurs on marine wintering grounds.…”
mentioning
confidence: 99%
“…Recent studies report elevated lead concentrations in eiders, a commonly hunted waterfowl, from the Yukon-Kuskokwim Delta region of western Alaska (11,12). The Alaska Native communities living around this region (e.g., Bethel) rely largely on a subsistence diet that includes waterfowl killed with lead shot.…”
Section: Introductionmentioning
confidence: 99%